Successful Treatment of Bronchial Fistula after Pulmonary Lobectomy by Endobronchial Embolization Using an Endobronchial Watanabe Spigot. (15th April 2015) - Machida, Yuichiro; Tanaka, Makoto; Motono, Nozomu; Maeda, Sumiko; Usuda, Katsuo; Sagawa, Motoyasu
Abstract : A bronchial fistula is one of the most serious complications that can occur following pulmonary lobectomy. We herein report a case of bronchial fistula that was successfully treated by endobronchial embolization using an Endobronchial Watanabe Spigot (EWS). A 72-year-old male underwent right lower lobectomy of the lung with nodal dissection for a pulmonary squamous cell carcinoma. A bronchial fistula developed 53 days after surgery. Tube drainage was performed, and air leakage was apparent. Under endoscopic observation, intrathoracic injection of indigo carmine revealed that a fistula existed at the peripheral site of the B 2 ai bronchus. After one EWS (small) was inserted into the B 2 a bronchus tightly using a bronchoscope, the air leakage was stopped. Pleurodesis was further carried out, the thoracostomy tube was subsequently removed, and the patient was discharged. Endobronchial embolization using an EWS is an option for the treatment of a bronchial fistula after pulmonary resection.